Urgency Of Career Women By Islamic Perspective - Dewi Riza Lisvi Vahlevi (Ekosiana Jurnal Ekonomi Syari ah, 2023)
Nowadays, a mother not only plays a role in taking care of the household, but also works. There are several factors that cause a mother to work, one of which is economic matters. From this, researchers want to dig deeper information about the incident. The purpose of this study was to determine the role of working housewives in improving family welfare and Islamic views on this phenomenon. This research uses descriptive qualitative methods and data collection techniques by interviewing and literature study. The results of this study are that working housewives can have an impact on the welfare of their families because they can financially support their husbands and their children's education. Even though they work they still pay attention to household matters. So, mothers do not do things that are contrary to what is in the teachings of Islam. Key Words : Ibu Rumah Tangga, Kesejaheraan Keluarga, Perspektif Islam